Solidification of shipyard solid waste using dolomite and rice husk ash as additives / Rosmawati Abdul Aziz - Abdul Aziz, Rosmawati (2005)
Industrial solid waste may pollute soil, air, surface water or underground water if it contains toxic substances. This pollution if do not properly managed can cause serious health risks and problem to the surrounding environment. In this study, solidification was used to treat industrial solid waste from Malaysian Shipyard Company. The physical and chemical stability of the waste was improved using cement-based solidification. Similar to conventional concrete production, industrial waste was used to replace sand with the proportions of 0% waste - 100% sand, 50% waste - 50% sand, 70% waste - 30% sand, and 100% waste - 0% sand proportions. 5, 10, 15, and 20% rice husk ash (RHA) and dolomite were added as additives and the effect of these materials on the strength and leaching of the concrete containing waste were investigated. Solidification was evaluated by carrying out compressive strength and leaching test. KH Method was also used in evaluating the effectiveness of the encapsulation technology, which determines the strength and leaching simultaneously. For compressive strength test, sample of 70% waste - 30% sand proportion was found to be the optimum ratio that gives the highest strength for both samples with and without additives. 100% waste - 0% sand also gives higher strength compared to control (0% waste - 100% sand). The results show, presence of dolomite, increased the concrete strength, with the optimum of 10% dolomite addition. However, addition of 20% dolomite gives weaker concrete. Same results of strength were obtained with the addition of RHA. Strength that gained with presence of dolomite gives higher strength when compared to RHA. For leaching test, after encapsulation, the leachability of contaminant were reduced for all samples of wastesand proportions with and without additives. For oil and grease, sample of 50% waste - 50% sand with 15% dolomite showed better result, which reduced at 83%. KH Method shows that the results are compatible to the standard method for testing strength and leaching. Through solidification, hazardous waste can be safely disposed into landfill or used as by-product.